Influence of fermented feed on lipid composition and volatile flavor profile of duck eggs: Insights from multi-omics analysis - Qishan Dong; Lizhi Lu; Tiantian Gu; Yong Tian; Yibo Zong; Jing Sun; Yu Huang; Qiuling Fu; Jun He; Tao Zeng (Food Chemistry: X)
This study employed a multi-omics approach to examine the impact of feed fermentation on the lipid profile and volatile flavor of duck eggs. Sensory evaluation and GC × GC-TOFMS analyses demonstrated that microbial fermentation in feed significantly reduced the off-odor of duck eggs. Among the thirty-nine differential volatile compounds identified, six—namely 3-methylbutanal, 1-octen-3-ol, hexanal, acetophenone, 2-heptanone, and 2-pentylfuran—were likely responsible for the alteration in yolk aroma. Lipidomics and metabolomics identified twenty-five key differential lipids (p < 0.05, VIP > 1.85) and a modified metabolic pathway associated with linoleic acid (LA), involving four metabolites. Correlation analysis revealed significant associations between LA-containing lipids (e.g., DG (18: 2/18:2)), LA metabolites, and differential volatiles (e.g., 3-methylbutanal) (p < 0.05). These results provide insights into the mechanisms underlying off-odor reduction and offer a potential strategy for enhancing the flavor profile of duck eggs.